The Major Stilbene Compound Accumulated in the Roots of a Resistant Variety of Phoenix dactylifera L. Activates Proteasome for a Path in Anti-Aging Strategy - Redouane Benabbes; Sabir Ouahhoud; Mohammed Moueqqit; Mohamed Addi; Christophe Hano; Cédric Delporte; Aminata P. Nacoulma; Véronique Megalizzi (Cells, 2022)
The main objective of the present study is to estimate, through differential analysis, various biological activities of total phenolics content in alcoholic extracts of three date palm varieties sensitive or resistant to Fusarium oxysporum. sp Albidinis. Here, stilbene products with antioxidant and bioactive capacities were evidenced in resistant variety Taabdount (TAAR). Furthermore, the methanolic fraction of the TAAR-resistant date palm variety contains a significant product, determined by LC-MS/MS and 1H, 13C NMR, belonging to the family of hydroxystilbenes, which exhibits antioxidant capacities, inhibits the mushroom tyrosinase activity, and activates and exerts a protective effect on hypochlorite-induced damage in 20S proteasome of human dermal fibroblast aged cells. Altogether, the present results indicate that hydroxystilbene present in resistant Phoenix dactylifera L. should be studied to understand the way that the stilbene could exert anti-aging ability.